Conflict Analysis in Kabarion Conservancy: Livestock Climate Systems Resilience Project, Baringo County - Mansurmoe Development Consultants Limited (CGIAR System Organization, 2024)
The report comprises a conflict assessment for Kabarion Conservancy, Bartabwa and Chemolingot Ward, Baringo County. The study was conducted from 31 August to September 3 2023. The main objective was to find a common approach to a conflict that has existed in the area for several years. The assessment applied a mixed- methods approach, comprising a literature review and qualitative data collected using key informant interviews and focus group discussions. The targeted group was the area’s local administrative personnel, community and youth.